2017
DOI: 10.1016/j.biocon.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for the effects of increased nitrogen deposition on fauna

Abstract: Effects of increased N deposition, caused by agricultural practices and combustion of fossil fuels in traffic and industry, have been studied in detail for soil and water chemistry as well as for vegetation and ecosystem functioning. Knowledge on fauna is limited to descriptive and correlative data for a small number of species or communities. Therefore, mechanisms behind effects of N deposition on animal species and diversity remain unclear, which hampers optimisation of nature restoration and conservation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 97 publications
0
62
0
1
Order By: Relevance
“…There may be at least three potential causes for the outbreak of C. dauricus in the present study. First, N addition stimulated plant growth, thereby increasing the food resources for herbivores (Nijssen, Wallisdevries, & Siepel, ; Ritchie, ). In this aspect, although N addition did not significantly increase ANPP in the present study, ANPP showed an increasing trend (Figure e).…”
Section: Discussionmentioning
confidence: 99%
“…There may be at least three potential causes for the outbreak of C. dauricus in the present study. First, N addition stimulated plant growth, thereby increasing the food resources for herbivores (Nijssen, Wallisdevries, & Siepel, ; Ritchie, ). In this aspect, although N addition did not significantly increase ANPP in the present study, ANPP showed an increasing trend (Figure e).…”
Section: Discussionmentioning
confidence: 99%
“…Although no substantial pollinator richness declines were detected during these early time periods, local density declines or changes in their foraging behavior might have already occurred, preceding the richness declines detected later on (Fig. In addition, the time lag detected for insects could be a response to changes in resource quality (Adler and Irwin 2011, Hoover et al 2012, Nijssen et al 2017, as discussed below. This suggests a time-lag for pollinator richness changes in relation to plants.…”
Section: Effect Of Resource Preferences On Historical Patterns Of Biomentioning
confidence: 94%
“…Impacts on plant community are well-recognized, including losses in species diversity (Stevens et al 2004, Bobbink et al 2010, and these may propagate to primary consumers (Stevens et al 2018). While there has been recent research into effects on herbivores (Nijssen et al 2017, Pöyry et al 2017, WallisDeVries and van Swaay 2017, the potential effects of soil eutrophication on those feeding on pollen and nectar (potential pollinators) are largely unexplored (Stevens et al 2018, but see Betzholtz et al 2013, Tamburini et al 2017, Ramos et al 2018. Such potential bottom-up effects could be mediated by reduction in nectar or pollen availability or quality (Petanidou et al 1999, Vanderplanck et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen can impact plant–pollinator interactions via a number of mechanisms, these can be grouped into two of the key pathways suggested by Nijssen et al. (); (1) changes in food plant quantity (through shifts in plant community composition), (2) nutritional quality, in addition a third pathway via changes to phenology. Competitive exclusion of more stress‐tolerant plant species has been shown to reduce the functional diversity of flowering plants (Helsen et al., ) with associated impacts on pollinator diversity (Biesmeijer et al., ; Potts, Vuliiamy, Dafni, Ne'eman, & Willmer, ).…”
Section: Impacts On Higher Trophic Levelsmentioning
confidence: 99%